Role of Insulin in Neurotrauma and Neurodegeneration: A Review - Shaughness, Michael; Acs, Deanna; Brabazon, Fiona; Hockenbury, Nicole; Byrnes, Kimberly R. (Frontiers in Neuroscience, 2020)
Insulin is a hormone typically associated with pancreatic release and blood sugar regulation. The brain was long thought to be ‘insulin-independent’, but research has shown that insulin receptors (IR) are expressed on neurons, microglia and astrocytes, among other cells. The effects of insulin on cells within the central nervous system are varied, and can include both metabolic and non-metabolic functions. Emerging data suggests that insulin can improve neuronal survival or recovery after trauma or during neurodegenerative diseases. Further, data suggests a strong anti-inflammatory component of insulin, which may also play a role in both neurotrauma and neurodegeneration. As a result, administration of exogenous insulin, either via systemic or intranasal routes, is an increasing area of focus in research in neurotrauma and neurodegenerative disorders. This review will explore the literature to date on the role of insulin in neurotrauma and neurodegeneration, with a focus on traumatic brain injury (TBI), spinal cord injury (SCI), Alzheimer’s disease (AD) and Parkinson’s disease (PD).